Pertambangan Nikel di Raja Ampat Perspektif Hukum Positif dan Hukum Islam - Tasya Almutia Ramadani; Nur Mumtahana; Sahruni; Kurniati (CV Global Research Publication, 2025)
Raja Ampat as the center of world marine biodiversity faces serious threats from nickel mining, including sedimentation, air pollution, ecosystem damage, and socio-economic impacts on coastal communities, thus creating a conflict between positive legal regulations that grant mining permits and Islamic legal principles on environmental conservation. This study aims to identify marine and terrestrial environmental phenomena resulting from the presence of mining in Raja Ampat, analyze the mechanisms of positive legal regulations in managing these impacts, and explore Islamic legal perspectives and solutions to formulate integrative policy recommendations. Using a qualitative normative juridical approach through secondary data literature study with comparative content analysis and source triangulation, the study found that PT Gag Nikel's activities caused net deforestation of 52.42 hectares, coral bleaching of up to 70%, heavy metal pollution that threatens the food chain, and the loss of fishermen's livelihoods; positive law shows the inconsistency of old regulations with the prohibition of mining on small islands, while Islamic law emphasizes the principle of caliphate, the prohibition of facade fi al-ard, la dharar wa la dhirar, and Maqashid Syariah to encourage conservation management such as ecotourism and sustainable fisheries. In conclusion, the integration of both legal frameworks can produce operational policies to stop mining exploitation, prioritize ecosystem preservation, and ensure the welfare of local communities, with implications for sustainable collaborative governance in conservation areas.